EARLY BLOOD CELL COUNT TEST (BCT) FOR SURVIVAL PREDICTION FOR NON-SMALL CELL LUNG CANCER PATIENTS TREATED WITH ATEZOLIZUMAB: INTEGRATED ANALYSIS OF 4 MULTICENTER CLINICAL TRIALS - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Jin, Su-Han; Tan, Fangya; Chen, Yu-Zhong; He, Si-Si; Shen, Gang; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Shen, Bo; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
Immune checkpoint inhibitor (ICI) therapy is a major breakthrough for non-small cell lung cancer (NSCLC) treatment given its high efficacy and tolerable toxicity. Although pre-treatment PD-L1 expression levels and tumor mutation burden (TMB) may serve as prognostic biomarkers for patient stratification, effective predictive biomarkers are lacking. Blood cell count test (BCT) is a routine, regular blood test conducted before and during treatment to provide a direct overview of the immune landscape based on the counts of various types of immune cells (ICs). For instance, previous studies showed that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) both indicate poor treatment outcomes of ICI therapy of NSCLC patients.<br
CRIS-Team WoS Importer:2022-04-15